Direito fundamental à boa administração pública municipal e compliance - Rheinheimer Filho, Ari (2024)
This dissertation is part of the New Paradigms of Law concentration area, in the line research program Social Relations and Dimensions of Power. The approach method is deductive and historical and monographic procedures are used. The study is built around the following problem: it is necessary to implement a compliance program at the municipal level to achieve the fundamental right to good public administration? Brazilian municipalities are entities federatives. This singularity allows them to have autonomy: legislative, self-organization, financial, political and administrative. In order to be able to exercise them fully, the principle-constitutional system established competencies of a material and legiferantes. Among the activities and policies developed by this entity, the fundamental right good public administration must be incessantly researched, becoming a duty of administration. The tructural complexity, its regional, extension and population density, the financial imbalance of municipalities, adding to the lack of commitment, unpreparedness and lack of knowledge by those in charge and the permanence of practices such as clientelism, political sponsorship and collusion in the conduct of actions and provision of public services, it becomes necessary to implement public management similar to corporate governance, risk management and compliance in private activities. Paper preponderant in this evolution was the implementation of the management reform in 1998, replacing the state bureaucratism and its procedural excesses, by techniques controlled by results and by society. Create this structuring through legal and regulatory aspects, provide access information, publicity and transparency of their actions and engagement of society and popular participation are essential. This way, it will be possible to develop compliance municipality with its set of procedures and compliance structures, with standards moral and legal, seeking to guarantee results through its public policies, complying with its duty to provide good administration, guided by risk management, ethics and transparency. Compliance is comprehensive and needs to be suitable for municipalities. In view of the above, it is up to the Municipality adopts and substantially adapts compliance, if it wants to guarantee the implementation and maintaining the fundamental right to good public administration as a state duty and a citizenship rights.